The association of emotional intelligence with sport injuries and receiving penalty cards among Iranian professional soccer players - Angoorani, H.; Najafi, S.; Sobouti, B.; Zarei, M.; Nejati, P. (Asian Journal of Sports Medicine, 2020)
Background: High emotional intelligence (EI) seems to be preventive for unconventional sports behavior within competitions leading prevention of sport injuries and also minimization of giving penalty cards.